Chemical control of weeds in sugarcane field - Apacible, Alejandro R.
Trials on post-emergence chemical control of weeds of sugarcane were conducted during the 1963-1964 crop milling season on sugarcane cultivar Coimbatore 330 (Co 330) on clay loamy soil at Canlubang Sugar Estate, Calamba, Laguna. Comparative result of eleven (11) different treatments including two controls indicated varying degrees of toxicity to the weeds growing in the sugarcane fields. The effect on the yield in terms of piculs sugar per hectare was used to reflect the efficacy of the different chemicals in the control of twenty-two species of grasses and broad-leaved weeds including the fast and hard to kill Aguingay (Rottboellia exaltata), Kogon (Imperata cylindrica var. Major), Kamote-kamotehan (Ipomoea trilioba), Pulang puwet (Echinochloa colonum), etc. Weeding by chemicals in controlling the weed growth in cane fields until close-in reduced the weed population that competes with sugar cane for moisture, light, food nutrients and space for the fast growth and heavy tillering of the cane plant. Of these treatments Karmex / Surfactant WK at 2.5 Kg./Ha. 0.5% surfactant (Vol/vol) was the most effective in controlling weeds and gave the highest sugar yields among the treatments. This is followed in effectivity by Gramoxone, Agral (dribble bar), Kuron, Telvar / Surfactant WK, Penatrol Dry Sodium Salt, Gesaprim 50 W. The other three herbicides Dowpon, Gramoxone Agrall 90, and Basfapon have hardly any effect as herbicides in this experiment. Productivity of sugar per hectare is greatly affected by the presence of weeds that compete with the plant cane. Throughout the experiment the difference in yields showed a range 3.31 to 128.47% increase in yields over the control. That some of the chemicals which were frequently used as pre-emergence are effective also as early post-emergence as shown in Table 1-c, p-60, T2, T10; T8, T4, T11, T5, T6, T3, and T9 (descending order).
Available to the general public.
Thesis (Doctor of Philosophy in Botany)--University of Santo Tomas, 1977.
Keywords: Sugarcane -- Diseases and pests; Noxious weeds